PENDAMPINGAN PENGGUNAAN APLIKASI FIGMA SEBAGAI ALAT DESAIN UI/UX UNTUK MENINGKATKAN LITERASI DIGITAL SISWA SMK NEGERI TUGUMULYO - Eli Suryani; Kiki Fitaloka; Firdaus Firdaus (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The development of digital technology today requires adequate digital literacy skills. This Community Service Program (PKM) took the form of mentoring on the use of the Figma application as a UI/UX design tool, aiming to enhance the digital literacy skills of students at SMK Negeri Tugumulyo. This PKM was also expected to develop students' UI/UX design abilities so they can compete in the creative industry. The target participants were 11th-grade students from the Software Engineering (RPL) department at SMK Negeri Tugumulyo. The implementation methods for this mentoring included lecture, discussion, demonstration, and Q&A session. The material covered an introduction to UI/UX design, its process stages, and how to utilize the Figma application. The activity concluded with a quiz with prizes to test participants' understanding. As a result, participants gained a better understanding of digital literacy, increased their knowledge about UI/UX design, and learned to utilize the Figma application as a UI/UX design tool. As a follow-up plan, more in-depth training will be conducted on the utilization and use of the Figma application as a UI/UX design tool, to prepare students for careers in the field of digital design.